Influence of Video Health Education on Knowledge and Attitudes toward Menopausal Nutrition. - Putri, Sabilla; Pipitcahyani, Tatarini Ika; Sukesi, Sukesi; Rijanto, Rijanto (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
Menopause is a condition with a decrease in reproductive physiological function in women which results in a decrease in ovarian function which can result in a reduction and possibly a loss of reproductive estrogen. This research is a type of quantitative research with a research design using Quasy experiment with a pre-test post-test control group approach of 32 respondents divided into treatment groups and control groups. By using the research design